2021
DOI: 10.29392/001c.28999
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the demand for vaccination through mHealth in Quetta City, Balochistan in Pakistan

Abstract: Background Balochistan is the largest province of Pakistan by area, and the least developed. It suffers from several political, tribal and border conflicts. The distances to health facilities for the catchment population are long with limited accessibility. Immunization is one of the most cost-effective interventions to prevent deaths from vaccine preventable diseases (VPDs), especially in children. While Pakistan has an overall routine immunization coverage of 66 per cent for fully immunized children (FIC), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…This has been effected more by low literacy rate and considerably low knowledge about vaccines making it difficult especially for women, to develop a basic understanding of vaccination and the importance of herd immunity. 8 Evidence has shown that individuals with better education have more awareness about vaccination resulting in less hesitancy and more likely to ensure complete immunization. 25 The strength of our study is that it is one of the early studies to explore WHO determinants and vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been effected more by low literacy rate and considerably low knowledge about vaccines making it difficult especially for women, to develop a basic understanding of vaccination and the importance of herd immunity. 8 Evidence has shown that individuals with better education have more awareness about vaccination resulting in less hesitancy and more likely to ensure complete immunization. 25 The strength of our study is that it is one of the early studies to explore WHO determinants and vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…7 Baluchistan is the most affected province of Pakistan by the problem of vaccine-hesitancy. 8 The coronavirus pandemic is not over, with new variants being discovered. Therefore, it is essential to understand who is at more risk and safeguard them.…”
Section: Introductionmentioning
confidence: 99%